2019
DOI: 10.1093/dote/doz080
|View full text |Cite
|
Sign up to set email alerts
|

Short- and mid-term outcomes of robotic versus thoraco-laparoscopic McKeown esophagectomy for squamous cell esophageal cancer: a propensity score-matched study

Abstract: SUMMARY Controversy exists on the advantages of robotic McKeown esophagectomy (RME) versus thoraco-laparoscopic McKeown esophagectomy (TLME). The aim was to evaluate the short- and mid-term outcomes of RME and TLME in the treatment of patients with esophageal squamous cell carcinoma (ESCC). A consecutive series of 652 patients, 280 in RME and 372 in TLME, who underwent minimally invasive McKeown esophagectomy for ESCC at our department from November 2015 to June 2018 was analyzed. A propensity s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
116
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(119 citation statements)
references
References 32 publications
3
116
0
Order By: Relevance
“…With respect to total LDN, Park et al [11] and Deng et al [30] retrospectively found that robot-assisted esophagectomy yielded more dissected lymph nodes than conventional MIE. However, several recent studies together with our study demonstrated that the number of total dissected lymph nodes was comparable between the two surgical approaches [13,21].…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…With respect to total LDN, Park et al [11] and Deng et al [30] retrospectively found that robot-assisted esophagectomy yielded more dissected lymph nodes than conventional MIE. However, several recent studies together with our study demonstrated that the number of total dissected lymph nodes was comparable between the two surgical approaches [13,21].…”
Section: Discussionsupporting
confidence: 59%
“…Theoretically, RAME achieves better short-term and oncological results than traditional MIE [ 21 ]. Using a magnified three-dimensional image, articulating forceps, and tremor filtering, RAME can overcome some limitations of traditional MIE.…”
Section: Discussionmentioning
confidence: 99%
“…58 A propensity score-matched comparison between 280 cases of robot-assisted MIE and 372 cases of thoracolaparoscopic MIE also showed promising safe and oncologically effective approaches with favorable short-and midterm outcomes in ESCC. 59 Therefore, it is assumed that the combination of NCRT with MIE may reduce postoperative morbidity and mortality. The ongoing CMISG1701 trial is a multicenter, prospective, randomized, phase III clinical trial, which was designed to confirm whether NCRT + MIE could yield better survival and decrease postoperative morbidity and mortality in patients with resectable locally advanced ESCC.…”
Section: Current Consensus and Controversy On Surgery-based Multimodamentioning
confidence: 99%
“…The advantages of robot-assisted MIE over video-assisted MIE are mainly reflected in the dissection of upper mediastinal lymph nodes and the protection of the RLN. In 2019, Yang et al [24]reported a consecutive series of 652 patients, 280 in robot MIE and 372 in video MIE, who underwent minimally invasive McKeown esophagectomy for ESCC. In spite of the similar results on total and thoracic lymph node dissection, robot-assisted MIE yielded more lymph nodes along the RLN (4.8 vs. 4.1, p = 0.012), as well as the higher incidence of recurrent nerve injury (29.2 vs. 15.1%, p < 0.001) when compared to TLME.…”
Section: Discussionmentioning
confidence: 99%